The role of transformational leadership on organizational commitment through the mediation of psychological well-being - Asterina, Rilis; Hastjarjo, Thomas Dicky (Psychological Research and Intervention, 2023)
This study aims to determine the role of transformational leadership on organizational commitment through the mediation of psychological well-being. Techniques of data collection is done through a survey by spreading scale consisting of organizational commitment, transformational leadership, and psychological well-being scale. Subjects in this study were 118 employees of the company construction in Yogyakarta areas. Data analysis was done by using multiple regression analysis. The analysis showed that the role of transformational leadership on organizational commitment fully mediated by psychological well-being with regression coefficient path c ' = 0.219 which is smaller than the regression coefficient path c = 0.376. This suggests that the role of transformational leadership as an independent variable on the organizational commitment as a dependent variable is reduced and becomes not significant with p â‰¥ 0.01 after controlling for variables mediator psychological well-being.